202k views
3 votes
Solve the following quadratic equation 6x^2-5x-4=0

User Joey
by
5.3k points

1 Answer

6 votes

Answer:

=

±

2

4

2

x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}

x=2a−b±b2−4ac​​

Once in standard form, identify a, b, and c from the original equation and plug them into the quadratic formula.

6

2

5

4

=

0

6x^{2}-5x-4=0

6x2−5x−4=0

=

6

a={\color{#c92786}{6}}

a=6

=

5

b={\color{#e8710a}{-5}}

b=−5

=

4

c={\color{#129eaf}{-4}}

c=−4

=

(

5

)

±

(

5

)

2

4

6

(

4

)

2

6

Explanation:

User CoredusK
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.